Anti-linealidad temporal y la realidad de la ficción : el vanguardismo de la revista Crononauta (1964) - David AJ Murrieta Flores (Amnis)
In 1964, the artist Alejandro Jodorowsky and the writer René Rebetez edited and launched Crononauta magazine in Mexico, proposed as a science fiction publication, and in which artists and writers such as Manuel Felguérez, Roland Topor, Fernando Arrabal, and Raquel Jodorowsky participated. As part of the artistic movements that were later denominated as « rupturistas » by the country’s art historiography, the magazine represents both an experiment and a thought model articulated around the connection between aesthetics and knowledge and its possibilities regarding the transformation of reality. It consists of an encounter between the so-called « Panic Movement » of which Jodorowsky was a founder and a notion of science fiction developed by Rebetez, which resulted in the privileging of the hybridization of divergent spaces and times. Through collage, understood as a mechanism of extraction and appropriation of contexts, and the use of a literary method authored by French writer Raymond Roussel, which produces novelty from repetition and doubles, Crononauta’s avant-gardism poses the disolution of the limits between present, past, and future in the possible transformative continuity between reality and fiction.The purpose of this article is to analyze how the aesthetic elements are intertwined with the political and social project of the magazine, a chaotic and ambiguous proposal with references ranging from Surrealism to the Utopian Socialism of the 19th century. In this respect, Crononauta’s position before the future uses science fiction as an aesthetic weapon akin to prophecy, destined to transform reality. It is similar to other avant-garde artistic developments like the « efímero pánico » – cousin of happenings – that would collapse distnictions between the proper of reality and the other of fiction : to apocaylptically end one world in order to birth another.